PERBEDAAN KEMANDIRIAN ANAK USIA DINI DITINJAU DARI SUBYEK PENGASUH (ORANGTUA DAN KAKEK NENEK) DI TK DHARMA WANITA PERSATUAN 1 SRIMULYO DAMPIT-MALANG - Amala, Nilta; Nurhayati (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
When parents are working, parenting turns to grandparents, they want their children to grow and develop into independent individuals. In Dharma Wanita Persatuan 1 Srimulyo Kindergarten, it is known that 30% of children are cared for by grandparents and 70% of children are cared for by their parents.This research uses quantitative method with descriptive research type. The sampling technique used was purposive sampling technique. This study used a sample of early childhood in TK Dharma Wanita Persatuan 1 Srimulyo Village who were cared for by their parents and grandparents. The data analysis method of this research is using statistical analysis with the help of the SPSS program.The results showed that most of the independence levels of children who were cared for by parents at Dharma Wanita Persatuan 1 Srimulyo Kindergarten had moderate independence, and most of the independence levels of children raised by grandparents had high independence.The results of this study obtained data that the average value of the independence of children who are cared for by parents is 255.07 and those who are cared for by grandparents is 276.16 then Ho is rejected, which means there is a significant difference between the independence of early childhood who are cared for by parents. and independence of early childhood who are cared for by grandparents. The value of the level of independence of early childhood who is cared for by grandparents is higher than that of early childhood who is cared for by parents.